HUBUNGAN GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI DENGAN KINERJA PAMONG BELAJAR DI SANGGAR KEGIATAN BELAJAR (SKB) - Abdul Rahmat, Ahmad Izzudin (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
The purpose of this research is to give further description how leadership factor and organizationalr cultural factor can contribute or related to the performance gained by the tutors in the organization by looking at (a) the relation between leadership style and tutor’s performance, (b) the relation between organizational culture and tutor’s performance, and (c) the relation between leadership style and organizational culture with tutor’s performance. This positivistic research employed survey method and conducted in Community Learning Center (SKB) Limboto, Gorontalo District, as from September through November 2014. The data were collected by distributing questionnaires to the tutors, interviewing informant, and studying the document and then analyzed using path analysis. The result of the study indicates (a) leadership style has significant relation with the tutor’s performance, (b) organization culture has significant relation with tutor’s performance, and (c) between leadership style and organizational culture simultaneously has significant relation with tutor’s performance.